"Transfer, Contestation and Conflict": How Italian regional and national governments claim and challenge authority in mandatory vaccination policies. (30th September 2020) - Rizzi, M; Attwell, K; Casigliani, V
Abstract: Background: This paper explores conflictual policy transfer in Italian vaccination policy 2007-2018. The region of Veneto formally suspended mandatory vaccination in 2007. Soon after, declining vaccination rates across the country sparked a public health crisis. Emilia Romagna adopted a new vaccine mandate for early education, which the national government adopted in 2017. Each policy decision invoked collaboration and contestation between governments. In showing the conflictual aspects of intra-state policy transfer, we offer lessons for multi-level health governance of contested issues. Methods: We used qualitative documentary analysis of parliamentary transcripts, legislation and government reports, supplemented with semi-structured key informant interviews, using the coding software NVivo 12. We applied theoretical and conceptual scholarship to develop an analytical framework drawing out the key mechanisms through which contestation and conflict take place. Results: Italian regional and national governments employed three key mechanisms to forcibly transfer or resist vaccination policy: ideas, evidence, and law. Ideas included "the nation", "herd immunity" and "science." Evidence included coverage rates and explanations of changes over time. Protagonists of Italy's coercive policy transfers used the law to claim and challenge authority. Contestations occurred in political and bureaucratic spheres. Discrepant historical and evidentiary narratives emerged between levels of government that had injected significant resources into acquiring or defending governance of vaccination policy. Conclusions: Scholarship has predominantly considered coercive policy transfer at a supra-national or inter-state level. We demonstrate the political blood-spilling within a country when divergent regional policies become contested in a situation of national crisis. 'Evidence' and 'law' can be open to differing interpretations, with 'ideas' shaping the context in which policies prevail.